Development of Crispy Roti Flour Using Riceberry Flour as Substitute for All Purpose Wheat Flour - Wrivutthikorn, Wattana (Burapha Science Journal, 2024)
Background and Objectives : Riceberry is an antioxidant and a good source of iron, calcium and vitamin E. Riceberry flour was used to increase nutrition value and partially substitute all purpose wheat flour in crispy roti flour. Therefore, the purpose of this research was to develop the crispy roti flour products in order to substitute all purpose wheat flour with 0% (as a control formula), 40%, 60% and 80% of riceberry flour. Methodology : The study of the physical and chemical properties of heated and unheated riceberry flour revealed that they were significantly different. Physical properties such as lightness, colour and texture, as well as chemical properties such as moisture content, water activity, crude fiber as well as anthocyanin and DPPH inhibition varied. Furthermore, microbiological properties including total plate count were also evaluated. In addition, the results of sensory evaluation of each product’s in terms of colour, odour, texture and overall acceptability were performed by 30 panelists using the 9-point hedonic scale. Main Results : With respect to the physical properties of lightness, redness, yellowness, hardness and fracturability, it was found that all experiments were significantly different (p<0.05). The lightness, redness, yellowness, hardness and fracturability exhibited a light purple to dark purple colour in the range of 17.99-62.29, 7.91-10.55, 5.61-33.85, 267.26-2517.96 N and 0.80-6.90 mm, respectively. As the amount of riceberry flour increased, lightness, colour and texture also significantly decreased. The chemical properties showed that they were significantly different, except for the moisture. The water activity, moisture content, crude fiber, anthocyanin and DPPH inhibition were in the range of 0.50-0.71, 1.28-3.62%, 0.35-2.15%, 0.00-22.09 mg/g dry weight and 0.00-45.11 mg eq trolox/100g, respectively. The microbiological results revealed that total plate count met the standard regulation according to the Thai Industrial Standards Institute crispy roti (CPS.503/2004). The sensory evaluation indicated that colour, odour, texture and overall acceptability of crispy roti product supplemented with 40% riceberry flour gave the highest scores of 7.57, 7.97, 7.67 and 7.87, respectively. Conclusions : In conclusion, higher amounts of riceberry flour used in order to replace all purpose wheat flour in the crispy roti flour product resulted in a high quality texture together with crude fiber, DPPH inhibition and anthocyanin.